The Influence of Village Apparatus Capacity on Village Fund Management Accountability with the Village Financial System (Siskeudes) as an Intervening Variable - Gloria Elizabeth Yoltuwu; Janet Wilsye Litualy (International Journal of Economics, Commerce, and Management, 2026)
This study aims to examine the effect of village apparatus capacity on accountability in village fund management, with the village financial system (SISKEUDES) as an intervening variable in Letti District, Southwest Maluku Regency. The research assessed whether the competence, knowledge, and administrative ability of village officials can improve transparent and accountable fund management. This study employed a quantitative approach using a saturated sampling technique, involving all 42 apparatus members as respondents. Data were collected through questionnaires and analyzed using multiple regression and the Sobel test to examine direct and indirect effects. The findings show that village apparatus capacity has a positive effect on village fund management accountability. This indicates that human resource capacity can support responsible planning, implementation, reporting, and evaluation of village funds. However, the village financial system does not significantly affect village fund management accountability. In addition, SISKEUDES does not function as an intervening variable in the relationship between village apparatus capacity and accountability. These results imply that strengthening human resource capacity remains more decisive than system use.